Heamatological parameters, endocrinological profiles, antioxidant and oxidative stress profiles of repeat breeding crossbred cows in Andaman and Nicobar Islands - PERUMAL, P; CHAURASIA, D; DE, A K; BHATTACHARYA, D; BHOWMICK, SNEHA; KUNDU, A; MISHRA, P C (The Indian Journal of Animal Sciences, 2021)
The present study was carried out to assess the effect of repeat breeding syndrome (RBS) on heamatological, antioxidant, oxidative stress and endocrinological profiles in crossbred cows under tropical island ecosystem of Andaman and Nicobar Islands. Each of the twelve number of cows was selected (which were affected with repeat breeding syndrome) as Group 2 and normal cyclic breeding cows as Group 1. These cows were maintained under similar type of managemental conditions. Heamatological profiles, antioxidant and hormone profiles were estimated by automatic blood analyser and commercial diagnostic kits, respectively. The result revealed that the crossbred cows with RBS suffered severe anaemia. The RBS affected animals showed significantly lower level of antioxidant profiles and significantly higher malondialdehyde (MDA) than the unaffected animal groups. Similarly, endocrinological profiles revealed that the RBS affected animals had significantly higher level of cortisol, prolactin and lower level of 17 Î²-estradiol (E2), progesterone (P4), follicle stimulating hormone (FSH), luteinizing hormone (LH), thyroxine (T4) and insulin like growth factor-1 (IGF-1) than the unaffected crossbred cows. The study concluded that the RBS was due to anaemia, lack of antioxidants, overproduction of free radicals and disturbances of endocrinological profiles in crossbred cows of Andaman and Nicobar Islands.